Helminth Infection in Pregnancy: Effect on Serum Albumin Level and Pregnancy outcome - Steven Ridwan; Sitti Wahyuni; Maisuri T Chalid (Indonesian Socety of Obstetrics and Gynecology, 2015)
Objective: To determine the prevalence of helminth infection in pregnant women and its effect on albumin levels and pregnancy outcome. Method: A prospective cohort study was conducted on third trimester pregnant women presenting for antenatal care in several hospitals in Makassar. Information on subject demography was recorded using short questionnaire. Stool samples were collected to determine the presence of helminth infection. Albumin levels were measured from maternal blood and cordâ€blood. Outcome of pregnancy was assessed upon delivery. Result: The prevalence of helminth infection in our subjects was 22.8%. Among 21 infected women, 17 were infected with Ascaris lumbricoides (80.9%), one with Trichuris trichiura and three with both Ascaris and Trichuris. The mean Ascaris lumbricoides intensity was 1769.3 epg (Range = 24â€11.688 epg). Helminth infections have no effect on either maternal or neonatal albumin levels (p=0.748 and p=0.480, respectively). Although it was not found to be significant (p>0.05), helminth infection seems to affect gestational age (OR 2.06, 95% CI 1.48â€2.86) and birth weight (OR 2.18, 95% CI 1.52â€3.14). Neonatal albumin level and pregnancy outcome were not affected by maternal albumin level. Conclusion: Helminth infection seems to affect pregnancy outcome in pregnant women in Makassar, but not through influence of albumin. Factors other than albumin level may responsible for such condition.